Metagenomic Functional Profiling Reveals Differences in Bacterial Composition and Function During Bioaugmentation of Aged Petroleum-Contaminated Soil - Pacwa-Płociniczak, Magdalena; Biniecka, Paulina; Bondarczuk, Kinga; Piotrowska-Seget, Zofia (Frontiers in Microbiology, 2020)
Our objective was to study the bacterial community changes that determine enhanced removal of petroleum hydrocarbons from soils subjected to bioaugmentation with the hydrocarbon-degrading strains Rhodococcus erythropolis CD 130, CD 167, and their combination. To achieve this, a community-level physiological profiling and high-throughput sequencing of the 16S rRNA gene were performed. The metabolic patterns of all bioaugmented soils differed from the control soil only at the beginning of the experiment. On the last day of the experiment, different metabolic activity was reported in the CD 167 soil in which the highest hydrocarbon loss was observed. Similarly, the changes in the bacterial community composition were most apparent the day after bacterial inoculation. These changes represented an increase in the percentage abundance of Rhodococcus and Pseudomonas genera. Surprisingly, members of the Rhodococcus genus were not present after day 91. At the end of the experiment, the bacterial communities from the CD 130, CD 167, and control soils had a similar structure. Nevertheless, the composition of the bacteria in the CD 130 + CD 167 soil was still distinct from the control. Metagenomic predictions from the 16S rRNA gene sequences showed that the introduction of bacteria had a significant influence on the predicted pathways (metabolism of xenobiotics, lipids, terpenoids, polyketides, and amino acids) on day one. On day 182, differences in the abundance of functional pathways were also detected in the CD 130 and CD 130 + CD 167 soils. Additionally, we observed that on day one, in all bioaugmented soils, the alkH gene was mainly contributed by the Rhodococcus and Mycobacterium genera, whereas in non-treated soil, this gene was contributed only by the Mycobacterium genus. Interestingly, from day 91, the Mycobacterium genus was the main contributor for the tested genes in all studied soils. Our results showed that hydrocarbon depletion from the analyzed soils resulted from the activity of the autochthonous bacteria. However, these changes in the composition and function of the indigenous bacterial community occurred under the influence of the introduced bacteria.